Analisis Dan Perancangan Sistem Informasi Penjualan Bahan Bangunan Berbasis Web Pada Toko Bangunan Daerah Tigaraksa Menggunakan Metode User Accptance Testing - Dede Kurniawan; Verri Kuswanto; Alexius Hendra Gunawan (ALGOR, 2023)
In this day and age, there are still many medium-sized businesses such as building shops that still do not use technology, thus causing a small scope of marketing and sales of products from the building store itself. To increase the scope of marketing and sales areas, one way is to take advantage of internet technology that is suitable to be applied to building stores. Building a store requires an online sales information system that is useful for store owners and potential buyers. Therefore, a sales information system was created that is available anytime, anywhere without time and region limits, called e-commerce. The methodology of the software development stages used in this study uses the Rapid Application Development (RAD) model. Rapid Application Development (RAD) is a focused method of developing software quickly, by repeating also on feedback that is also repeated. The results of this study are expected to help make it easier for potential buyers to make purchases and can help building shop owners in selling their goods. User Acceptance Testing (UAT) is a verification process to ascertain whether the completions made in the system are suitable for the user. Based on the User Acceptance Testing (UAT) test that has been carried out on 30 respondents, it shows the results that the satisfaction given from using this website is 85.3%.